Estudo das transições de fase nos ferroelásticos Pb8O5(XO4)2 com X=V e As - Oliveira, Euzenil Almeida de (2007)
This work presents the results obtained from the study of crystals belonging to the family Pb8O5(XO4)2 whit X= V and As. Several experimental techniques were applied to investigate the sequence of structural phase transition. At room temperature, Pb8O5(AsO4)2 crystallizes in a monoclinic face centered structure belonging to the C2/m (C32h) space group, with four molecules per unit cell (Z=4). Measurements of the Raman scattering have been performed in this compound to obtain a description of the room temperature phonon spectrum and its temperature dependence in the range from 300 K to 773K. We have observed that the Pb8O5(AsO4)2 shows a structural phase transition at approximately 500 K, which was not reported before in the literature. Raman spectroscopy, polarization microscopy and differential scanning calorimetry (DSC) have been used for study the thermal evolution of the phonon spectrum and crystalline structure of the Pb8O5(VO4)2. This compost show a second order phase transition at 426 K and a first order one at about 523 K. Measurements of the polarization microscopy of the ferroelastic domains show the presence of two different types of domain, a wedge-shaped or V and a needle-shaped. A new phase transition was identified in the low temperature (231 K), being the first evidence of transformations of this type in a compound of this family.